Advanced reliability modeling : part II - Dohi, Tadashi; Kaio, Naoto; Yun, Won Young (Journal of Quality in Maintenance Engineering ;, 2006)
This e-book contains selected papers invited/presented in the Asian International Workshop on Advanced Reliability Modeling (AIWARM) which was held in Hiroshima, Japan, August 26-27, 2004. This e-book is intended to share the ideas and results from the workshop with more reliability researchers and practitioners.